Pressure ulcer prevention using an alternating-pressure mattress overlay: the MATCARP project. (1st September 2020) - Meaume, Sylvie; Marty, Marc
Abstract : Objective: The primary objective was to assess the incidence of pressure ulcer (PU) in patients at high risk of PU and lying between 15–20 hours per day on an alternating-pressure mattress overlay (APMO). Secondary objectives were the patient's satisfaction with the comfort of the APMO, patient acceptance of its sound level, and the care team's assessment of its use and the moisture level. Method: This prospective observational study was conducted in three rehabilitation centres and two nursing homes between June 2016 and March 2017. To be included, patients should not have PU at baseline and present a high risk of PU (Braden score between 10–15). The primary endpoint was the percentage of patients in whom a PU developed over a 35-day period. Results: A total of 83 patients were included in the study. Neurological disease was responsible for the reduced mobility of 44 (53.7%) patients, 10 patients (12.0%) dropped out (one patient for a serious adverse event (femoral neck fracture) considered not to be related to the APMO, four patients for adverse events, two of which were considered to be related to APMO and five for other reasons, including, in one case, discomfort with the APMO. These patients were considered in the analysis. Over the study period, 1.2% (1/83) (95% confidence interval (CI): 0.03 to 6.53) of patients developed a PU. Patient satisfaction with the comfort of the APMO, patient acceptance of its sound level, and the care team's assessment of its use were considered satisfying for most patients. Conclusion: Based on the findings of this study of a low incidence of PU in participating patients, the use of an AMPO is recommended in high-risk patients lying for between 15–20 hours a day.